4A.02: STENTING OF ATHEROSCLEROTIC RENAL ARTERY STENOSIS DOES NOT IMPROVE CLINICAL OUTCOMES IN PATIENTS PRESENTING WITH CONGESTIVE HEART FAILURE, AN ANALYSIS OF THE CORAL TRIAL. (June 2015) - Yu, S.; Brewster, P.; Ren, K.; He, W.; Xiang, K.; Tuttle, K.; Jamerson, K.; Dworkin, L.; Cutlip, D.; Solomon, S.; Murphy, T.; Dagostino, R.; et al.
Abstract : Objective: In some guidelines congestive heart failure is an indication for renal artery stenting. We sought to determine, in patients enrolled with a history of congestive heart failure (CHF), the effect of renal artery stenting on clinical outcomes in the Cardiovascular Outcomes in Renal Atherosclerotic Lesions (CORAL) trial. Design and method: The CORAL trial is a prospective, international, multicenter clinical trial that randomized participants with atherosclerotic renal artery stenosis, who received optimal medical therapy, to stenting versus no stenting. Optimal medical therapy included treating blood pressure and diabetes to goal, use of an angiotensin receptor-blocking drug, a statin, and anti-platelet therapy. Clinical data from patients with a history of CHF were analyzed using SAS and R software. Glomerular filtration (eGFR) was estimated using the serum creatinine-cystatin-C-CKD-EPI equation. Patients were followed for a median of 43 months (IQR, 31 to 55). Blood pressure was measured in triplicate, after 5 minutes seated quietly, with an oscillometric device. Results: A history of CHF was present at enrollment in 123 of 931 subjects, 69 in the medical therapy group and 54 in the medical therapy + stenting group. Neither the composite event rate (41% vs. 48%, p = 0.51), rate of CHF admission (20% vs. 26%. p = 0.112) nor the rate of cardiovascular death (16% vs. 17%, p > 0.99) differed between medical therapy only and the stent + medical therapy groups. At 2-years follow-up no differences were observed between medical therapy and medical therapy + stent for systolic blood pressure (SBP) (136 ± 26 vs. 136 ± 18 mmHg, p = 0.94) or eGFR (56 ± 23 vs. 56 ± 23 ml/min, p = 0.96). In the longitudinal analysis of eGFR and SBP, neither stent treatment (p = 0.212 and p = 0.9801, respectively) nor the interaction between stent treatment and time (p = 0.429 and p = 0.551, respectively) were significant. Conclusions: Renal artery stenting and optimal medical therapy, when compared to optimal medical therapy only, did not reduce the risk of fatal and nonfatal cardio-renal events in patients that were enrolled with history of congestive heart failure in the CORAL trial. Furthermore, stent treatment of CHF patients did not affect kidney disease progression or blood pressure control.